2012
DOI: 10.1007/s10719-012-9435-9
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of free Neu5Ac-containing complex-type N-glycans in human pancreatic cancers

Abstract: We have analyzed the structures of glycosphingolipids and intracellular free glycans in human cancers. In our previous study, trace amounts of free N-acetylneuraminic acid (Neu5Ac)-containing complex-type N-glycans with a single GlcNAc at each reducing terminus (Gn1 type) was found to accumulate intracellularly in colorectal cancers, but were undetectable in most normal colorectal epithelial cells. Here, we used cancer glycomic analyses to reveal that substantial amounts of free Neu5Ac-containing complex-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…Most recent studies, however, have shown that similar sialyl-fOSs are accumulated in human pancreatic (33) or prostate cancers (34) but not in normal epithelial cells, thus suggesting that these glycans can serve as useful tumor markers. The mechanisms by which these glycans are accumulated in cancer cells are not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Most recent studies, however, have shown that similar sialyl-fOSs are accumulated in human pancreatic (33) or prostate cancers (34) but not in normal epithelial cells, thus suggesting that these glycans can serve as useful tumor markers. The mechanisms by which these glycans are accumulated in cancer cells are not understood.…”
Section: Discussionmentioning
confidence: 99%
“…Structural analyses of oligosaccharides associated with pancreatic cancers revealed, unlike colorectal cancer cells, the presence of a variety of free Neu5Ac-containing complex-type N -glycans from three out of the fi ve cases (Table 12.2 ) (Yabu et al 2013b ). The relative amounts of these free Neu5Ac-containing complex-type N -glycans were comparable to or much higher than those of GSLs in most, but not all, pancreatic cancers.…”
Section: Free Oligosaccharidesmentioning
confidence: 96%
“…This type of glycan is an effective biomarker for pancreatic cancer detection. 24 With these characteristics in mind, the key to constructing a complex-type glycan-targeted material is designing a molecular receptor capable of recognizing and discriminating the core glycan fragment composed of four monosaccharide residues, namely, Neu5Ac-Gal-GlcNAc-Man. In this respect, nature has inspiration for the saccharide receptor design, for example, Maackia amurensis leukoagglutinin displays a strong but A biomimetic design for a sialylated, glycan-specific smart polymer Z Chen et al specific binding with sialylated tri-saccharide (that is, Neu5Ac-α(2-3) Gal-β(1-4)GlcNAc).…”
Section: Introductionmentioning
confidence: 99%